Analisa Peranan Pengetahuan Konsumen dalam Mempengaruhi Keputusan Menjadi Nasabah pada Bank Syariah - Diawati, Prety (Universitas Pendidikan Indonesia, 2010)
The core study is focused on factors influencing decision to become customer, covering knowledge of customers. Based on the problem, the analysis revealed in research is how knowledge of customers on decision to become customers either or simultinuously. The method used in this research is Explanatory Survey Methode, by questioners data collection technique in Likert category of five-scale. Data sources are acquired based on customers’ samples of saving of Bank Syariah Bukopin Bandung Branch Office. Data processing technique used is path analysis.Keyword: consumer knowledge, Decision to become customer. The result of research shows descriptively that the level of customers, knowledge is in medium category. While the result of statistic test by using path analysis; there is positive influence between customers, knowledge either partially or simultinuously on decision to become customers of saving program of Bank Syaria Bukopin Bandung Branch office